Exploration of Managerial Conflict In A Maternal Hospital - Youandi, Abdi Agus; Hariyanti, Tita (STIKes Maharani Malang, 2018)
The performance of âXâ Maternal Hospital (RSIA) with a leading field in Obstetrics and Gynecology. But tragically, the performance has gradually decreased. Â The research is to reveal the managerial conflicts in this hospital. This research uses phenomenology study approach through an interview. Besides interview, direct observation and its surrounding is also performed. Managerial conflicts resulted in human resource problems. It caused turnovers of employees. While some loyal employees handled this conflict in a peaceful manner, others were demotivated and tended to react destructively. Managerial conflict has an impact on a turnover, demotivation, and destructive behavior. Managerial conflict must be well-resolved to prevent the decrease of operational and financial performance of RSIA.